A retrospective cohort study of hospital versus home care for pregnant women with preterm prelabor rupture of membranes1. Issue 2 (27th February 2017) - Palmer, Lynne; Grabowska, Kirsten; Burrows, Jason; Rowe, Hilary; Billing, Erin; Metcalfe, Amy
Abstract: Objective: To compare maternal and neonatal outcomes between in‐hospital management and prepartum care at home (PCAH) among women with preterm prelabor rupture of membranes (PPROM) before 34 weeks of pregnancy. Methods: In a retrospective study, data were analyzed from women who experienced PPROM between 23 and 34 weeks of pregnancy, and received care from two hospitals in British Columbia, Canada, between April 2007 and March 2012. Women were included if they had been stable in hospital for at least 72 hours and met eligibility criteria for PCAH. Management of PPROM differs at the centers: at one, women are monitored in hospital, whereas PCAH is used at the other. Outcomes were compared between management strategies. Logistic regression was used to assess severe maternal morbidity and neonatal morbidity/mortality after adjustment for pregnancy length at PPROM. Results: Among 176 included women, 87 received PCAH and 89 were managed in hospital. There was no difference in severe maternal morbidity (adjusted odds ratio [aOR] 0.64, 95% confidence interval [CI] 0.35–1.17) or neonatal morbidity/mortality (aOR 0.63, 95% CI 0.31–1.30). Latency increased and length of stay decreased with PCAH ( P< 0.001 for both). Conclusion: Maternal and newborn outcomes were similar between women who received PCAH and those who were managed in hospital. The reduced resource use in PCAH might lead to cost savings without compromising outcomes. Abstract : As compared with in‐hospital treatment, prepartum care at home for PPROM might result in cost savings with no difference in maternal or neonatal outcomes.